The interaction between protocatechuic aldehyde and human serum albumin using three-dimensional fluorescence techniques. Issue 3 (2011) - Tian Tian, Jing Jing; Chen Chen, Changyun Changyun; Xue Xue, Mengwei Mengwei
Abstract : The binding mechanism between protocatechuic aldehyde (PA) and human serum albumin (HSA) was investigated by fluorescence spectroscopy at different temperatures. It is proved that the fluorescence quenching of HSA by PA is not results of the formation of PA–HSA complex. The equilibrium constant K and the number of binding sites n were measured at different temperature by fluorescence quenching method. The standard enthalpy change (Δ H ) and the standard entropy change (Δ S ) of this interaction process were calculated to be 114.02 kJ · mol −1, 541.92 J · mol −1 ·K −1, respectively. According to the interaction between PA and HSA of thermodynamic parameters Δ H and Δ S, the major acting force can be measured. The synchronous fluorescence spectra shows the microenvironment of tryptophan residue is changed and the hydrophobicity is increased. Through three-dimensional (3D) fluorescence spectra can get some valuable structure changing information.